2015
DOI: 10.3389/fpsyg.2015.00426
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal adminsitration of oxytocin in postnatal depression: implications for psychodynamic psychotherapy from a randomized double-blind pilot study

Abstract: Oxytocin is a neuropeptide that is active in the central nervous system and is generally considered to be involved in prosocial behaviors and feelings. In light of its documented positive effect on maternal behavior, we designed a study to ascertain whether oxytocin exerts any therapeutic effects on depressive symptoms in women affected by maternal postnatal depression. A group of 16 mothers were recruited in a randomized double-blind study: the women agreed to take part in a brief course of psychoanalytic psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…The latter finding is in line with previous links suggested between hormonal status and PTSD risk in women (Garcia et al 2018). No additional effects of daily OT during the treatment period of 12 weeks on depression or on attachment-like emotional traits in postpartum depressed mothers were found in a small trial of Clarici et al (2015). Only self-centeredness during treatment was significantly lower in the OT group compared with placebo (Clarici et al 2015).…”
Section: )supporting
confidence: 90%
“…The latter finding is in line with previous links suggested between hormonal status and PTSD risk in women (Garcia et al 2018). No additional effects of daily OT during the treatment period of 12 weeks on depression or on attachment-like emotional traits in postpartum depressed mothers were found in a small trial of Clarici et al (2015). Only self-centeredness during treatment was significantly lower in the OT group compared with placebo (Clarici et al 2015).…”
Section: )supporting
confidence: 90%
“…Indeed, only a few months after birth, these parents have the chance to interact with a lively newborn that they can see and touch. This aspect, together with the child’s positive reaction to surgery and medical treatment, give the parents hope, mitigating their fears of death and illness (Clarici et al, 2015; Tripani et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Empirical research has shown that parents’ intra-psychic dynamics during the perinatal period have an impact on the development of representations and interactive capabilities in the months following birth (Siddiqui and Hägglöf, 2000). Numerous studies in the field highlighted the importance of triadic family interaction as one of the most relevant factors in structuring the baby’s psychosocial development (Parke and Buriel, 1998) in various salient aspects, such as attachment (Erdman and Caffery, 2003), school adjustment (McHale and Rasmussen, 1998), psychopathological development (Jacobvitz et al, 2004; Clarici et al, 2015; Gatta et al, 2017), and theory of mind (Favez et al, 2012). However, studies on the influence of defect diagnosis on parental capacity in the time span between pregnancy and postpartum period are still very scarce (Skari et al, 2006; Giuliani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As we mentioned at different other occasions [45], within the last few years there was an increase in the number of research groups and general interest for better understanding of the possible beneficial effects exerted especially by intranasal oxytocin on the main neuropsychiatric diseases, with a focus on schizophrenia [54], depression [55], frontotemporal dementia [56], autism [57], or anxiety-related behavior [58].…”
Section: Oxytocin Relevancementioning
confidence: 99%